Investigation on the potential of dried blood stain for the detection of amphetamine type stimulants by enhanced methods of liquid chromatography tandem-mass spectrometry / Fathiah Ahmad Zubaidi - Fathiah , Ahmad Zubaidi (2020)
The investigation on the potential of dried blood stain for Amphetamine Type Stimulants (ATS) has been divided into four major parts, from which independent conclusions are drawn. The first part is the development and validation of a novel method for the simultaneous determination of the drugs using liquid chromatography with electrospray ionization tandem mass spectrometer (LC-ESI-MS/MS). The method is enhanced from normal Multi-Reaction Mode (MRM) to Multi-Reaction Mode-Enhanced Product Ion Mode- Multi-Reaction Mode 3 (MRM-EPI-MRM3) and tested in whole blood specimens (WBS), dried blood stain (DBS) and urine specimens as well as applied to real forensic cases in Malaysia. The ATS are confirmed by their retention times, as well as the respective ions in MRM mode, complemented with higher level of detection using EPI (library matching) and unique identification by combinations of ions in MRM3 mode. The second part covers another novel technique of Flow Injection Analysis (FIA)-MRM3 spectrometry for the differentiation of prime critical isomeric compound related to ATS; methamphetamine and phentermine. The technique is designed to shorten the analysis time to 2 min by eliminating the chromatography/separation part and focusing on the strength of MRM3 mode in spectrometry part. From the validation and real samples testing, the both of isomeric compounds are successfully discriminated and gives a new dimension on high throughput analysis in the forensic field. While the third task evaluates the reliability of DBS versus WBS technique using Mean Concentration Ratio and Bland-Altman statistical analysis. he results show no significant difference for the ATS in the both techniques proving that the DBS method can be applied interchangeably in the future. The evaluation of DBS has been extended to testing the stability and efficiency of the medium during storage period in part four. The variants studied include the time and temperature in Malaysia for 6-month period of DBS storage. The study proves good stability and efficiency of ATS drugs and establishes the performance of DBS as an alternative and innovative method to be implemented in forensic analytical purposes.